The Theory of Neutralization of Crime and Its Relationship with Restorative Justice” - esmaehl rahimi nejad; mehdi aghayari; gholamreza gholipour (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2015)
Restorative justice as a new approach in the field of criminal law seeks to compensate damages resulted from crimes and repair interrupted relationships. The important point here, is uderstanding the theoretical bases of this concept. In the present research, the theory of neutralization of crime was studied as one of the theoretical bases of restorative justice in order to determine the relationship between these two. According to this theory, the offender despite being aware about wrongfulness of his action, tries to neutralize the shameful picture of the crime through five techniques: “denial of the victim”, “denial of responsibility”, “denial of damages”, “loyalty to the upper commitments” and “condemnation of condemners”, and make it seem reasonable to pave the way for committing crime. Restorative justice programs make it possible for delinquent person to understand the wrongfulness of his act and its justifying techniques in a participatory and community-based process and accept the responsibility of his actions. This research analyses this issue with descriptive and analytical approach and by review article method.